ANALISIS DAN DESAIN PERANGKAT PEMBELAJARAN MODEL PROBLEM BASED LEARNING BERBASIS HOTS DAN LITERASI PADA PEMBELAJARAN IPA - Alfian Erwinsyah; Ramli Utina; Frida Maryati Yusuf; Erni Mohamad; Muhamad Iksan (LP2M IAIN Sultan Amai Gorontalo, 2022)
The purpose of this study is to develop a problem-based learning model based on higher order of thinking skills. The research method used is the ADDIE Research and Development model which is limited to the Analysis and Design Steps. The tools developed are RPP, LKPD, Assessment Instruments. The results of the research are that the HOTS-based and Literacy-based PBL learning device products have real characteristics in learning, arranged systematically with PBL syntax, will develop HOTS and student literacy. and the final product of the learning device meets the valid criteria seen from the validator score. Keywords: Learning Tools, ADDIE, PBL, HOTS